x=(coseca+cota)(cosecb+cotb)(cosecC+cotC) y=(coseca-cota)(cosecb-cotb)(cosecC-cotC) if x=y then prove that .... x=y=+-1
Answers
Answered by
0
Answer:
Step-by-step explanation:
(1/sin+cos/sin) (1/sin+cos/sin) (1/sin+cos/sin)
Sin cod sin /sin2o cansal sin and sin
1 keep it as result 1 same for y also keep it as result 2 from 1and2 x=y=+-1
nikhildhariwal27:
bro can u elobarate
Answered by
0
Answer:
Step-by-step explanation:
Similar questions
English,
8 months ago
Science,
1 year ago
English,
1 year ago
Chemistry,
1 year ago
Political Science,
1 year ago